PENDIDIKAN RAMAH ANAK DAN IMPLIKASINYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MIN 1 BITUNG - Normawati Sunusi (Jurnal Ikhtibar Nusantara, 2026)
Child-Friendly Education is an educational approach that places students as the main subjects in the learning process by upholding children's rights, safety, comfort, and protection from all forms of violence. This study aims to examine the implementation of Child-Friendly Education and its implications for the learning process of Islamic Religious Education at MIN 1 Bitung. This research uses a descriptive qualitative research method with data collection techniques through observation, interviews, and documentation. The subjects of this study were Islamic Religious Education teachers and students at MIN 1 Bitung. The results of the study indicate that the implementation of Child-Friendly Education in the madrasah has a positive impact on the learning process of Islamic Religious Education, including increased student participation, the creation of a comfortable learning atmosphere, and the development of moral values and Islamic character among students.